Effect of Tensile Stress on Cavitation Erosion and Damage of Polymer. (November 2015) - Hibi, M; Inaba, K; Takahashi, K; Kishimoto, K; Hayabusa, K
Abstract: Cavitation erosion tests for epoxy, unsaturated polyester, polycarbonate, and acrylic resin were conducted under various tensile stress conditions (Tensile-Cavitation test). A new testing device was designed to conduct the Tensile-Cavitation test and observe specimen surface during the experiment based on ASTM G32. When tensile stress of 1.31 MPa was loaded on epoxy resin, cracks occurred on the specimen after 0.5 hours during cavitation erosion. When no tensile stress was loaded on the epoxy resin, the damage was general cavitation erosion only. As well as the epoxy resin, unsaturated polyester resin applied tensile stress of 1.31 MPa and polycarbonate resin of 6.54 MPa indicated erosion damages and cracks. When tensile stress of 6.54 MPa was loaded on acrylic resin, the erosion damage was almost the same as the results without tensile stress. We confirmed that anti-cavitation property of epoxy resin was higher than those of acrylic and polycarbonate without tensile stress while the damage of epoxy resin was much serious than that of acrylic resins under tensile stress loadings.